Retrieving self-vocalized information: An event-related potential (ERP) study on the effect of retrieval orientation - Rosburg, Timm; Johansson, Mikael; Sprondel, Volker; Mecklinger, Axel (Brain and cognition, 2014)
Retrieval orientation refers to a pre-retrieval process and conceptualizes the specific form of processing that is applied to a retrieval cue. In the current event-related potential (ERP) study, we sought to find evidence for an involvement of the auditory cortex when subjects attempt to retrieve vocalized information, and hypothesized that adopting retrieval orientation would be beneficial for retrieval accuracy. During study, participants saw object words that they subsequently vocalized or visually imagined. At test, participants had to identify object names of one study condition as targets and to reject object names of the second condition together with new items. Target category switched after half of the test trials. Behaviorally, participants responded less accurately and more slowly to targets of the vocalize condition than to targets of the imagine condition. ERPs to new items varied at a single left electrode (T7) between 500 and 800ms, indicating a moderate retrieval orientation effect in the subject group as a whole. However, whereas the effect was strongly pronounced in participants with high retrieval accuracy, it was absent in participants with low retrieval accuracy. A current source density (CSD) mapping of the retrieval orientation effect indicated a source over left temporal regions. Independently from retrieval accuracy, the ERP retrieval orientation effect was surprisingly also modulated by test order. Findings are suggestive for an involvement of the auditory cortex in retrieval attempts of vocalized information and confirm that adopting retrieval orientation is potentially beneficial for retrieval accuracy. The effects of test order on retrieval-related processes might reflect a stronger focus on the newness of items in the more difficult test condition when participants started with this condition.